PERLINDUNGAN HUKUM HAK CIPTA FILM ATAS PENAYANGAN DI BIOSKOP DRIVE THRU TANPA IZIN - Laras Ayu Aprilia (2021)
This research aims to illustrate a form of copyright infringement of the work of the film due to the emergence of various violations, especially against the film, which is unwittingly committed by the public. The study also sheds light on the legal protection of a film that has been screened without permission at a drive thru cinema since the pandemic. The research method used in this writing is a juridical normative that rests on legal material in the form of positive legal rules or norms related to copyright. In this study using the statutory approach (statute approach). The results showed that drive thru cinemas that screen films without the permission of creators and copyright holders do not violate moral rights but have violated the economic rights of creators and rights holders related to the communication of creation and violations can be punished with a maximum penalty of 3 (three) years imprisonment and a maximum fine of Rp500 million.